Gambaran Fear of Missing Out (FoMO) pada Mahasiswa Magister Psikologi Universitas Semarang - Eko Joko Nugroho; Esty Putriana Dewi; Pia Alfia; Rini Sugiarti; Fendy Suhariadi (EduInovasi: Journal of Basic Educational Studies, 2025)
Currently, the ease of access to technology has greatly facilitated human activities and communication throughout the day, simply by using a smartphone. Students using the internet as one way to seek information, both academic and non-academic. The internet is no longer just a tool for finding information but also provides opportunities for everyone to observe the activities of others, which may be perceived as more valuable than their own experiences. Through the internet, social media enables users to communicate without being limited by time and place. On the other hand, excessive use of social media can have negative effects, such as Fear of Missing Out (FoMO). This study aims to understand the depiction of Fear of Missing Out (FoMO) among active social media users who are students in the Magister's Program in Psychology at Semarang University, using a quantitative method where the analysis is based on statistics, and the collected data primarily takes a numeric or measurable form.The sampling technique used in this research is cluster random sampling, employing a group sampling method according to specific groups or regions, with the research population being active students in the Magister's Program in Psychology at Semarang University during the 2024/2025 academic year, totaling 68 individuals. The instrument used as a measurement tool in this research is an adapted version of the Fear of Missing Out Scale by Przybylski, Murayama, Dehaan, & Gladwell (2013), translated by Helmi (2020). The results of this study indicate that, in general, the Magister’s Psychology students at Semarang University who are active in the 2024/2025 academic year have low to moderate levels of FoMO.